2022
DOI: 10.4274/tao.2022.2022-2-14
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Clinical Role of Contrast Enhancement on Magnetic Resonance Imaging in Patients with Bell’s Palsy

Abstract: Objective: To investigate the prognostic value of the magnetic resonance imaging in Bell’s palsy patients. Methods: Patients who were diagnosed and treated with Bell’s palsy between October 2013 and March 2016 retrospectively selected. House–Brackmann grades, pre- and post-treatment pure tone audiograms, stapedial reflexes were analyzed and magnetic resonance imaging (MRI) scans with gadolinium-based contrast agents were evaluated. Contrast-enhanced segments of the faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Although clinical and neurophysiological improvements in facial nerve function during recovery from Bell's palsy were associated with the disappearance of facial nerve enhancement, the presence of enhancement on the initial MRI scan was suggested to not necessarily indicate a poor prognosis for recovery [ 10 ]. Yücel et al reported that there was no significant correlation between pre-treatment HB grades and enhancement and between clinical recovery and enhancement [ 17 ]. Song et al reported that quantitative analysis of the facial nerve on both the lesion side and the normal side, which allowed for more accurate measurement of facial nerve enhancement in patients with facial palsy.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical and neurophysiological improvements in facial nerve function during recovery from Bell's palsy were associated with the disappearance of facial nerve enhancement, the presence of enhancement on the initial MRI scan was suggested to not necessarily indicate a poor prognosis for recovery [ 10 ]. Yücel et al reported that there was no significant correlation between pre-treatment HB grades and enhancement and between clinical recovery and enhancement [ 17 ]. Song et al reported that quantitative analysis of the facial nerve on both the lesion side and the normal side, which allowed for more accurate measurement of facial nerve enhancement in patients with facial palsy.…”
Section: Discussionmentioning
confidence: 99%
“…[13] However, another study reported contrast enhancement of the facial nerve had no effect on the severity and prognosis of Bell palsy. [14] This study was based on the registration ledger of facial nerve palsy, but there was a limitation in that detailed data were obtained by reviewing the medical records retrospectively. In addition, since the results were from a single tertiary care hospital and all participants were Korean, it may not be generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] However, another study reported contrast enhancement of the facial nerve had no effect on the severity and prognosis of Bell palsy. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%